Study guides

Q: What does x2 plus 11x plus 10 equals x2 plus 13x equal?

Write your answer...

Submit

Related questions

13x + 15 = 11x - 5 2x = -20 x = -10

13x+9

Since 7x + 13x +2x + 8 is an expression (there is no equal sign), there is no answer as to what x equals. However, this expression can be simplified to 22x + 8.

it equals 13X.

Y=13/11x + 12/11

x + 13x + 10x = 50 - 6

13x

If you mean: 6x-4x-2+11x then it can be simplified to 13x-2

7 + 13x = -9 ie 13x = -9 - 7 x = -16/13 or "Minus one and three thirteenths"

If you mean 13x-11y = -12 then y = 13/11x +12/11

13x - 9y - 10

13x = -156 so x = -12

2x - 13x + 42 = x +ax + b a + b = 2(x - 6.5x + 21) = 34 = a + b

2x - 13 x = 24 -11x = 24 -11x/-11 = 24/-11 x = -2 2/11

x=-(29/11)

X = 12

x2 + 13x + 36 = 0 so (x+4)(x+9) = 0 so that x = -4 or x = -9

7+3w-13x

-x2 - 11x + 26= -x2 - 13x + 2x + 26= (2x - x2) + (26 - 13x)= x(2 - x) + 13(2 - x)= (2 - x)(x + 13)

If -14 is the y intercept then it is: y = -1/13x -14

It is a linear equation in a single unknown variable, x.

x2 + 13x = -30 ∴ x2 + 13x + 30 = 0 ∴ (x + 3)(x + 10) = 0 ∴ x ∈ {-3, -10}

42 + x2 = 13x ∴ x2 - 13x + 42 = 0 ∴ (x - 6)(x - 7) = 0 ∴ x ∈ {6, 7}

13x 32 plus 5x can be expressed mathematically as 173x/32.

-x2 - 11x + 26 = -(x2 + 11x - 26) = -(x2 - 2x + 13x - 26) = -[ x(x - 2) + 13(x - 2) ] = -(x + 13)(x - 2) = (x + 13)(2 - x)